Мовно-політичний світогляд Івана Пулюя - Фаріон, Ірина; Farion, Iryna (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розкрито мовно-політичний світогляд Івана Пулюя за його нещодавно виданими листами. Серед предмета досліджень – доля видатної особистості як шлях сповідування соборної і самостійної Української Держави крізь призму захисту української мови; родинне життя як приклад збереження на чужині рідної мови; боротьба за український університет; представництво українця у владі і засудження мовно-національної асиміляції та угодовства. The article attempts to shed light on Ivan Puliui’s linguistic and political ideology based on the analysis of his recently published letters. The subject of the research includes the discription of this prominent figure’s fate aimed at substantiating that it was a way of establishing united and independent Ukrainian State. The investigation of the problem has been performed in the terms of the Ukrainian language defense, family life as an example of native language preservation in a far- off land and struggle for establishing the Ukrainian university in foreign country. The letters demonstrate the consistent linguistic and ethno-national ideology of a thinker, who not only outstripped his time, but has great impact on the modern realities with typical for them devastating linguistic bifurcation and cultivating cosmopolitism and globalization. The thinker interprets the language as a determinative culture-bearing and state-building factor and claims that among the main reasons of Ukrainian national identity absence is Ukrainian statelessness.
Ivan Puliui’s Linguistic and Political Ideology
Keywords: лінгвоперсонологія; мовно-політичний світогляд; етнонаціональна свідомість; націєцентризм; мовно-політична ситуація; linguopersonology; language and political ideology; language and ethno- national consciousness; nation-oriented aspect; linguistic and political situation